Thrifting Practices as a Form of Sustainable Fashion in Indonesia: A Fiqh Muamalah Analysis - Afdhalia, Afifah Nabila; Fathurohman SW, Oman (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2025)
The practice of thrifting (buying and selling second-hand clothing) is gaining popularity in Indonesia but still faces challenges from Islamic law and environmental sustainability. Ideally, this practice can support the principles of sustainable fashion and meet the requirements of fiqh muamalah. However, some thrifting practices involve illegal imported goods that harm the local industry and violate the provisions of buying and selling. This study aims to analyze the compatibility of thrifting practices with the principles of fiqh muamalah and their impact on environmental sustainability. This article falls under qualitative library research. The methodology used is normative legal study. The research findings show that the sale and purchase of second-hand clothing in thrifting is permissible (mubah) as long as it meets the conditions and requirements of a valid transaction and does not contain harmful elements. If defects in the goods are not disclosed, the transaction becomes invalid, and khiyar (option to cancel) must be exercised. This practice also supports environmental sustainability by reducing textile waste, but it is prohibited if it involves illegal imported goods that contradict national policies and hinder the growth of the local industry.